(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
A nurse call system is a vital element within healthcare facilities, designed to enhance the safety and welfare of patients by offering a prompt and dependable means for them to request assistance when necessary. The proposed nurse call system utilizes an Arduino microcontroller paired with a Bluetooth module, enabling wireless communication with mobile phones. Specifically, the communication occurs between the Android device and the alarm system via Arduino Uno boards. Bluetooth serves as an efficient method for establishing this connection. When a patient activates the call button on the mobile application, a signal is transmitted to the microcontroller, which subsequently alerts the staff members. This model is deemed highly cost-effective, as smartphones are widely accessible to patients. The only requirement is to install the calling system on the patients’ mobile phones to maintain connectivity with nurses and staff.